Inventário de barreiras e facilitadores ao empreendedorismo: construção e validação de uma medida psicométrica - Souza, Gustavo Henrique Silva de (2014)
The identification of the entrepreneurial behavior comes finding it difficult to measure, since the results and instruments, developed so far, don't have presented a behavioral model of universal compatibility for the entrepreneur and not have followed some recommendations found in the literature for research in entrepreneurship, considering circumstantial and behavioral elements. Accordingly, in order to fill this gap, this dissertation reports a study on the construction and validation of the inventory of barriers and Facilitators to entrepreneurship, Act for 8 independent factors: intention to Undertake; Risk; Access to Capital; Innovation; Opportunity; Leadership and management; Relationship network; Passion. The study part of the premise that the individual is faced with barriers and Facilitators, behavioral and contextual order (social and environmental), that can propel or inhibit the action to take. Through validation techniques, a low-cost instrument (pencil and paper) and easy to apply (self-report), with appropriate psychometric parameters.